2011
DOI: 10.1179/2047773211y.0000000002
|View full text |Cite
|
Sign up to set email alerts
|

Geographical structuring ofTrypanosoma cruzipopulations from ChileanTriatoma infestanstriatomines and their genetic relationship with other Latino American counterparts

Abstract: In order to obtain more information about the population structure of Chilean Trypanosoma cruzi, and their genetic relationship with other Latino American counterparts, we performed the study of T. cruzi samples detected in the midgut content of Triatoma infestans insects from three endemic regions of Chile. The genetic characteristics of these samples were analysed using microsatellite markers and PCR conditions that allow the detection of predominant T. cruzi clones directly in triatomine midgut content. Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…12 Recent studies using three microsatellites for T. cruzi genotyping reported that from 12 T. infestans found in houses in the Metropolitan Region that were tested, five had TcI, five had TcIII, and two had hybrid lineages. 18 In this study, using the four probes described, we found no unknown lineages. Thus, it is unlikely that there is a genotype that has not been detected.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…12 Recent studies using three microsatellites for T. cruzi genotyping reported that from 12 T. infestans found in houses in the Metropolitan Region that were tested, five had TcI, five had TcIII, and two had hybrid lineages. 18 In this study, using the four probes described, we found no unknown lineages. Thus, it is unlikely that there is a genotype that has not been detected.…”
Section: Discussionmentioning
confidence: 45%
“…17 More recently, the presence of TcIII was documented in Triatoma infestans from Chile by using three microsatellite markers, with TcI, a hybrid (TcV + TcVI), and unknown lineages. 18 Chagas disease is endemic to Chile. Three sylvatic triatomine species have been described: the kissing bugs M. spinolai Porter 1934, M. gajardoi Frias, Henry and Gonzalez 1998, and M. parapatrica.…”
mentioning
confidence: 99%
“…Thus, if the predominant clone was homozygous and the sample had three additional alleles (a total of four alleles), it was concluded that the minimum number of clones (MNC) is 3, because an odd number of alleles was considered as another clone. By contrast, in the same sample if the predominant clone was heterozygous, it was concluded that the MNC is 2, as described (Venegas et al 2011).…”
Section: Genotyping Of the Predominant T Cruzi Clone In Each Dna Samplementioning
confidence: 88%
“…The determination of the genotype of the predominant T. cruzi clone in samples containing multiple alleles per locus was conducted taking into account the distance and the height in FU of the two highest peaks, the major and secondary peaks directly in the electropherogram, as described (Venegas et al 2011).…”
Section: Genotyping Of the Predominant T Cruzi Clone In Each Dna Samplementioning
confidence: 99%
See 1 more Smart Citation